Engineering multi-layered skeletal muscle tissue by using 3D microgrooved collagen scaffolds. (December 2015) - Chen, Shangwu; Nakamoto, Tomoko; Kawazoe, Naoki; Chen, Guoping
Abstract: Preparation of three-dimensional (3D) micropatterned porous scaffolds remains a great challenge for engineering of highly organized tissues such as skeletal muscle tissue and cardiac tissue. Two-dimensional (2D) micropatterned surfaces with periodic features (several nanometers to less than 100 μm) are commonly used to guide the alignment of muscle myoblasts and myotubes and lead to formation of pre-patterned cell sheets. However, cell sheets from 2D patterned surfaces have limited thickness, and harvesting the cell sheets for implantation is inconvenient and can lead to less alignment of myotubes. 3D micropatterned scaffolds can promote cell alignment and muscle tissue formation. In this study, we developed a novel type of 3D porous collagen scaffolds with concave microgrooves that mimic muscle basement membrane to engineer skeletal muscle tissue. Highly aligned and multi-layered muscle bundle tissues were engineered by controlling the size of microgrooves and cell seeding concentration. Myoblasts in the engineered muscle tissue were well-aligned and had high expression of myosin heavy chain and synthesis of muscle extracellular matrix. The microgrooved collagen scaffolds could be used to engineer organized multi-layered muscle tissue for implantation to repair/restore the function of diseased tissues or be used to investigate the cell–cell interaction in 3D microscale topography.